Spare change - Parker, Robert B., 1932-; Burton, Kate. (New York : Random House Audio, 2007)
When the Spare Change Killer resurfaces after three decades they call on retired cop, Phil Randall who headed the original investigation and he calls in his daughter Sunny for help. She's sure she has found the killer but has no proof. When the next two victims resemble Sunny her father insists she drop the case, but she wants to create a trap to catch him.
Read by Kate Burton.
Unabridged.
Compact discs.
13 17 19
Keywords: Randall, Sunny (Fictitious character) -- Fiction; Women private investigators -- Massachusetts -- Boston -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction; Audiobooks